2015
DOI: 10.1007/s10067-015-3014-y
|View full text |Cite
|
Sign up to set email alerts
|

Education for patients with rheumatoid arthritis in Latin America and the Caribbean

Abstract: Patient education is highly recommended in rheumatoid arthritis (RA) to support patient management. The challenge is to adhere to the recommendations for providing health education to RA patients in Latin American and the Caribbean (LAC) countries taking into account factors such as patient health illiteracy, lack of rheumatologists, and lack of resources including access to disease-modifying antirheumatic drugs (DMARDs). As existing educational material in regional languages is not readily available and inade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
0
6
0
5
Order By: Relevance
“…Several studies have reported that patient education and provision of accurate information improve treatment outcomes [ 27 , 28 , 29 ]. The Internet represents a cost-effective medium through which patients can be educated.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that patient education and provision of accurate information improve treatment outcomes [ 27 , 28 , 29 ]. The Internet represents a cost-effective medium through which patients can be educated.…”
Section: Discussionmentioning
confidence: 99%
“… 9 , 10 Additionally, implementing educational programs to improve overall patients’ health through accompaniment and empowerment has helped reduce the effects of the disease when used as an additional intervention to conventional health care. 10 A study conducted in 2005 with Colombian patients showed how an educational intervention could improve knowledge and physical function in patients with RA. 11 The Pan American League of Associations of Rheumatology (PANLAR) recommends the existence of educational programs for people with RA from the initial diagnosis and on an ongoing basis, based on a formal, regular assessment of needs.…”
Section: Introductionmentioning
confidence: 99%
“…11 The Pan American League of Associations of Rheumatology (PANLAR) recommends the existence of educational programs for people with RA from the initial diagnosis and on an ongoing basis, based on a formal, regular assessment of needs. 10 Despite the call for educational intervention for RA patients in countries such as Colombia, there are few programs for patients and caregivers. Regular assessment of needs includes exploring the expectations of patients on RA.…”
Section: Introductionmentioning
confidence: 99%
“…7 Furthermore, in Latin American countries exists inequalities in health care, for example few rheumatologists are available and, consequently, a high workload and short time per visit ensue, which negatively affects patient's education during their medical visits. 8 For this reason, individuals interested in their health consult topics such as self-monitoring, lifestyle changes, quality of life and disease course.…”
Section: Introductionmentioning
confidence: 99%